Strategic Foresight to Optimize Exports of Cotton Garments from the Peruvian Textile and Apparel Sector to the US Market - Caballero-Yataco, Ariana Fernanda; Massucco-Bustios, Marcello Paolo; Ruiz-Ruiz, Marcos Fernando (LACCEI, 2025)
The objective of this research was to analyze the exports of Peruvian textile and clothing sector to the United States market for the year 2030. This analysis identified a target scenario, outlining strategic projections that forecast an annual growth of at least 5% in the market share of Peruvian cotton garments. The study employed a non-experimental design with a descriptive and propositional scope, incorporating structural analysis through the MICMAC tool. This method, which relies on expert consensus within the sector, identified four key factors: informality, investment in R&D, utilization of installed production capacity, and product attractiveness. These factors, when interacting with key social actors—such as business owners, government entities, and the National Society of Industries—generate strategic synergies. Additionally, SMIC-Prob software was used to construct future scenarios. The main findings suggest that implementing the proposed strategies could result in a 25.42% increase in the total export value of cotton garments to the U.S., while fostering sustainable growth in the sector through cleaner production practices and optimized logistics routes. This study provides the sector with a prospective framework as a strategic decision-making tool, offering deeper insights into the effects of economic and social factors on industrial competitiveness. Future research directions include applying the model to similar sectors and conducting international comparative studies.